Rancang Bangun Sistem Sentral Kontrol Kandang Ayam Close House Berbasis Arduino Dan Haiwell Cloud Scada - Rofi Nur Andriansyah; Misbah Misbah; Rini Puji Astutik (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Closed house chicken coop is an innovation from the development of technology in the livestock sector. In closed house chicken coops, many arrangements and adjustments to environmental conditions in the chicken coop are carried out which are expected to increase broiler chicken production. In this study, researchers created a centralized control system on 2 closed house chicken coops to make it easier for broiler chicken entrepreneurs to monitor and control the closed house chicken coops owned by the entrepreneur through one place, without having to go directly to the closed house chicken coop to monitor and control the chicken coop which of course will be quite draining time and energy. This study uses Haiwell Cloud Scada as an interface device connected to the Arduino Nano microcontroller, DHT-22 sensor as a humidity and temperature detector sensor, MQ-135 sensor as an Ammonia gas detector, water level sensor as a reader of the remaining chicken drinking water level, IR sensor as a reader of the remaining chicken food level, DC fan which has 2 functions, namely inlet and exhaust in the chicken coop. Servo motor as a silo damper controller to fill chicken food from the silo to the chicken feeder located in the chicken coop.